Weighted salience allocation to goals in the unc-method (2013)
The KAOS (Knowledge Acquisition autOmated Specifi cation) goal diagram can be used to hierarchically represent and analyze organizational goals. In the context of the UNC-Method, such goals are often written in the aforementioned diagram by using a set of verbs denoting achievement, in order to represent the organizational goals and requirements. Nowadays, the importance of the goals is only established by the diagram hierarchy. However, requirements engineering considers other elements as well as the hierarchy in such a matter. On the other hand, there are proposals that assign importance to the goals on other diagrams, but they neglect the hierarchy and the type of verb that is used in wording. These reasons lead us to propose in this paper, a method for allocating weighted salience to KAOS diagram goals, in the context of the UNC-Method. We consider the verb type and the hierarchy. We explain this proposal by means of a lab study.